2020
DOI: 10.1038/s41467-020-16241-5
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulation by complement receptor 3-dependent human monocyte TGF-β1-transporting vesicles

Abstract: Extracellular vesicles have an important function in cellular communication. Here, we show that human and mouse monocytes release TGF-β1-transporting vesicles in response to the pathogenic fungus Candida albicans. Soluble β-glucan from C. albicans binds to complement receptor 3 (CR3, also known as CD11b/CD18) on monocytes and induces the release of TGF-β1-transporting vesicles. CR3-dependence is demonstrated using CR3-deficient (CD11b knockout) monocytes generated by CRISPR-CAS9 genome editing and isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…Multiple immune cells, aside from neutrophils, harbor receptors capable of recognizing exposed ß(1,3)-glucan and chitin and initiating an immune response. These cell types include important immune modulators such as monocytes, macrophages, dendritic cells and host epithelial cells [ 7 , 14 , 34 , 38 , 55 ]. Our data have already shown increased immune activation of murine macrophages in vitro in response to exposure to unmasked STE11 ΔN467 cells ( Fig 3D ), and it is likely that tissue resident and infiltrating macrophages play a similar role in recognizing and initiating an immune response against unmasked fungal cells within the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple immune cells, aside from neutrophils, harbor receptors capable of recognizing exposed ß(1,3)-glucan and chitin and initiating an immune response. These cell types include important immune modulators such as monocytes, macrophages, dendritic cells and host epithelial cells [ 7 , 14 , 34 , 38 , 55 ]. Our data have already shown increased immune activation of murine macrophages in vitro in response to exposure to unmasked STE11 ΔN467 cells ( Fig 3D ), and it is likely that tissue resident and infiltrating macrophages play a similar role in recognizing and initiating an immune response against unmasked fungal cells within the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…small β-glucan particles with a backbone length below seven glucose units cannot bind to dectin-1, and soluble β-glucans cannot initiate clustering of dectin-1 in immunological synapses, and consequently cannot activate this receptor [ 39 ]. It is noteworthy, however, that soluble β-glucans are able to bind to the complement receptor 3 and support humoral immune responses [ 40 , 41 ]. When taken current viewpoints together, both soluble and insoluble β-glucan fractions are capable of supporting immune responses, yet we argue that the β-glucan activity towards the production of chemo-attractants and potentially towards a cellular immune response is expected to be linked to insoluble β-glucans.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis of apoptotic bodies enhances TGF-β production, which is a well-known pro-fibrogenic cytokine and has pro-apoptotic function in the liver. Recently it has been identified that apoptotic bodies induce the release of TGF-β transporting monocytic extracellular vesicles [ 123 ]. Engulfment of apoptotic bodies by HSCs induces NADPH oxidase and is associated with liver fibrosis in vivo [ 124 ].…”
Section: Role Of Apoptotic Bodies In Hepatic Fibrosismentioning
confidence: 99%